Analisis Hasil Tangkapan Bubu Dasar Berdasarkan Lokasi Penangkapan Ikan di Perairan Seram Bagian Barat, Maluku - Haruna, Haruna; Hehanussa, Kedswin G.; Tuhumena, Lolita (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
Several factors influence the number and type of fish caught in a trap, including the size of the trap, fish activity, mobility, design, bait, soaking time,provision of shelter, moon phase, visibility of the trap in the water material, andtype of funnel. It is important to identify problems related to trap placement so thatthe productivity of fish resources can be optimal. This research aims to analyze thecomposition of fish species caught, length at first capture, and differences in catchrate of bottom traps based on different fishing locations. The research was carriedout from April to October 2023 in Talaga Nipa Hamlet, Waisala District, and WestSeram Regency using experimental fishing methods. The results of the research showed that there were 20 species of fish caught in the waters of Sanahuni Hamlet (Location A), with the most dominant type of fish being Pterocaesio tile, namely31.40%. Meanwhile, in the waters of Haya Pulo Hamlet (Location B), 16 species offish were caught, with the most dominant species being Scarus rubroviolaceus at22.86%. On average, caught fish such as Caesio cunning, Scarus rubroviolaceus andCaesio caerulaurea are caught before they reach maturity. The bottom trap catchrate in the waters of Sanahuni Hamlet (Location A) is higher than in the waters ofHaya Pulo Hamlet (Location B). Differences in the number and types of fish caughtin traps can be influenced by various factors, such as fish migration, foodabundance, oceanographic conditions, trap design and construction, depth ofoperation of fishing gear, and damage to coral reefs due to destructive bomb fishing.